Simulação de produtividade de milho em diferentes épocas de semeio em Arapiraca, Alagoas, pelo modelo AquaCrop - Anjos, Franklin Alves dos (2011)
The maize (Zea mays L.), due to its importance in human and animal diet, is one of the most widespread crop in the world. In Brazil, it is cultivated in almost all regions, due to this, has been the focus of agrometeorological modeling for decades. The AquaCrop model was used in this work in order to simulate the total biomass and daily yield, and get the corn crop forecast for the region of Arapiraca, Alagoas. The model uses the canopy cover (CC), instead of leaf area index (LAI) as a basis for separate calculations of the plant transpiration and evaporation of soil water. The productivity is calculated as the product of biomass and harvest index (HI). The input data of model experiments were performed by Medeiros (2008), in Batingas town in the country of Arapiraca-AL. For four seasons of sowing, the results of soil water storage simulated by the model AquaCrop tended to be similar to those observed variation. However, for the third sowing date had observed the storage maximum value (171.66 mm) at 35 DAE, whereas the maximum simulated (115.0 mm) occurred at 24 DAE. For the final yield biomass (kg ha-1) the maximum and minimum values observed (simulated) ranged from 13.059 (11.861) and 9.873 (8.306) for 3rd and 4th season of planting, respectively. The simulated grain yield was between 4.406 and 2.069 kg ha-1 for the 3rd and 4th sowing time, underestimating by 2.0% (3rd SS) and overestimated by 5.1% (4th SS). The overestimation of the 4th season of sowing due to the adjustment of the depth of the root system at 0.75 m, where for the other seasons of sowing depth considered was 0.60 m (MEDEIROS et al., 2008). The AquaCrop model is a tool to predict corn yield of the AL Bandeirante variety. This procedure allows for adequate estimation of grain yield with 18 days prior to harvest in the Agreste region of Alagoas, providing end users of the model program storage, logistics and marketing of grain crop to be harvested.